3(-10)=2(2(-10)+7)

Simple and best practice solution for 3(-10)=2(2(-10)+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-10)=2(2(-10)+7) equation:


Simplifying
3(-10) = 2(2(-10) + 7)

Multiply 3 * -10
-30 = 2(2(-10) + 7)

Multiply 2 * -10
-30 = 2(-20 + 7)

Combine like terms: -20 + 7 = -13
-30 = 2(-13)

Multiply 2 * -13
-30 = -26

Solving
-30 = -26

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 100+x^2=0 | | 12p+3=104 | | 3m+zr=r-7g | | 2xcos(2x)-x^2+4x-4=0 | | 2/5(6a-3)=1/7(5-9)-2 | | -2.2-m=13.2 | | -2.2-m=13.32 | | -2.2-m=13.3 | | A(n)=5+(n-1)6 | | 25x-21=11x | | 2.9q-4.7-5.6q=-1.7q-4.7 | | .875x-y=0 | | 8x+9-5x-15=0 | | y=.875x | | 9p-3=5p+5 | | 1/3(3x-9)=60 | | 6(3+x)=5(c-6) | | Z=12i | | 9(3y*3y)=10(3y) | | (x+9)(x+9)=648 | | 2+3x-3x^3=0 | | 1.1=logx | | 5x(squared)+43=x-1(5x+6) | | x^2+18x-567=0 | | 300=8990000000*(.0000000001/x) | | 300=8.99*10^9(.1*10^-9/x) | | 2x-9(-0)=14 | | 2(2r-1)=7(r+7) | | 8n-17=231 | | 5x+35=x+71 | | 3x^2+16x-48=0 | | R(x)=(x/x^2-49) |

Equations solver categories